2018
DOI: 10.1007/s10142-018-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional evolution of an auxin efflux carrier PIN1 and its functional characterization in common wheat

Abstract: Particularly PIN1, PIN protein-mediated rate-limiting auxin distribution plays a critical role in plant differentiation. Although well-characterized in Arabidopsis, little is known about the structural and functional relationship of the PIN1 gene among other plants. Here, we report that the gene structure remained conserved among bryophytes and angiosperms while the gene size varied by ~ 17%. Although the positions were conserved, highly variable intron phase suggests preference for specific regions in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…It was reported that virus-induced gene silencing of the TaPIN1 genes resulted in 26% reduction in plant height [32]. Multiple sequence alignment revealed that the TaPIN1 genes in the study by Singh et al [32] were similar to TaPIN1-7b in the phylogenetic analysis of our study (Fig. 1a).…”
Section: Discussionsupporting
confidence: 71%
“…It was reported that virus-induced gene silencing of the TaPIN1 genes resulted in 26% reduction in plant height [32]. Multiple sequence alignment revealed that the TaPIN1 genes in the study by Singh et al [32] were similar to TaPIN1-7b in the phylogenetic analysis of our study (Fig. 1a).…”
Section: Discussionsupporting
confidence: 71%
“…The M. polymorpha genome encodes five PIN genes (Bowman et al ., 2017). Only one, Mp PIN1 (Mp3g21660), also referred to as Mp PINZ in some previous publications, is orthologous with AtPIN1 and is predicted to be plasma membrane‐localised (Bennett et al ., 2014a; Singh et al ., 2019). The other four (Mp PIN2 / 3 / 4 / 5 ) each possess a short central hydrophilic loop, a feature associated with loss of plasma membrane localisation (Bennett et al ., 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that virus-induced gene silencing of the TaPIN1 genes resulted in 26% reduction in plant height [ 32 ]. Multiple sequence alignment revealed that the TaPIN1 genes in the study by Singh et al [ 32 ] were similar to TaPIN1-7b in the phylogenetic analysis of our study (Fig. 1 a).…”
Section: Discussionmentioning
confidence: 99%